Use of amino-naphthoquinones for production of antimicrobial textiles - Hong Li; Chao Ding; Yingchao Ji; Ying Wang; Qiuhong Wang (Functional Materials, 2016)
This study described a method for enhancing the durability of amino-naphthoquinones embedded on cotton fabrics by creating aldehyde groups in the molecular structure of cotton cellulose. These aldehyde groups undergo intermolecular coupling with the amino group to form imines whereby naphthoquinones are covalently bonded to the cotton cellulose. The results suggest that these antibacterial compounds are tightly bound to the cotton fabric and impart to the fabric antibacterial properties, which retain their antibacterial activity after 15 laundry cycles. Such type of antimicrobial finish can find wide application in the health and hygiene textile sector.